Shaping the future(s). Civil society and itineraries of personal commitment in Tunisian democratic transition - Giovanni Cordova (EtnoAntropologia, 2021)
The Arab Spring has forced observers to associate the southern shore of the Mediterranean with social and political dynamism, even though a great deal of uncertainty surrounds the whole area. The present contribution is dedicated to processes of civic and political participation occurring in Tunisia. These processes of political subjectivation present an evident reference to the speculative imagination of the future. By considering the biographies of social actors, I will focus on itineraries of personal commitment, which take shape within the framework of the heterogeneous Tunisian civil society.